Copyright Claims Board sebagai Mekanisme Efektif Penyelesaian Sengketa Hak Cipta Digital: Komparasi dengan Amerika Serikat dan Relevansinya bagi Indonesia - Queennifika Azzahra; Ade Syaharani Arief; Fadiyyah Salsabila (Jurnal Hukum Lex Generalis, 2025)
This study stems from copyright issues arising from advances in digital technology, which often lead to violations in the production, distribution, and publication of copyrighted works without the permission of the copyright owner. The researcher wanted to determine the effective mechanisms for resolving digital copyright disputes through the Copyright Claims Board (CCB) in the United States and how relevant they are in Indonesia. This study uses normative legal and comparative legal methods. This study obtained results related to effective mechanisms for resolving digital copyright issues in Indonesia by referring to similar resolutions in the United States through the CCB institution. In conclusion, this study shows that Indonesia is considered ineffective in resolving digital copyright disputes, so it needs to learn from the United States with its special institution that works effectively compared to litigation, namely the CCB, as well as the existence of special regulations such as the Digital Millennium Copyright Act (DMCA).